Persepsi Orang Tua Terhadap Pemerolehan Bahasa Inggris Anak Usia Dini - Iman Nurjaman; Titi Rachmi (Jurnal Ilmiah Wahana Pendidikan, 2019)
This study aims to determine parental perceptions of the acquisition of English in early childhood. This research was conducted using a qualitative method, using interview techniques for 40 parents of early childhood students. The results showed that 80% (32 parents) had the perception that acquiring English in early childhood was very important and needed to be taught early